The Effectiveness of Advanced Cardiopulmonary Resuscitation Training Using Multimedia Teaching Materials on Knowledge, Attitudes, and Practical Skills in Advanced Cardiopulmonary Resuscitation Among Nursing Students - Kantawong, Eakachai; Amattayakong, Chonticha; Yotsurin, Paweena; Oupra, Roshinee; Nonmeatawat, Chayatida (Journal of Nursing and Public Health Research, 2025)
A quasi-experimental one-group pretest-posttest study aimed to evaluate the effectiveness of advanced cardiopulmonary resuscitation (ACLS) training using multimedia teaching materials on the knowledge, attitudes, and practical skills of nursing students. The sample, selected through simple random sampling, consisted of 30 nursing students from Boromarajonani College of Nursing, Chiang Mai. The training program incorporated multimedia teaching materials, including an educational video on ACLS, a digital ACLS manual, scenario-based simulation videos, and a virtual simulation for hands-on ACLS skill training. Data collection tools included a general information questionnaire, knowledge assessment, attitude assessment, and practical skills evaluation. Descriptive statistics were used for general data analysis, Wilcoxon Signed-Rank test for knowledge and skills assessment, and paired t-test for attitude scores. Results showed that after training, participants had significantly higher mean scores in knowledge (z = -4.79, p-value < 0.001), attitudes (t = -7.98, p-value < 0.001), and ACLS skills (z = -4.90, p-value < 0.001) compared to pre-training. These findings suggest that multimedia-assisted ACLS training effectively enhances nursing students’ knowledge, attitudes, and skills.